Development of Intergeneric Canine Embryo Using Bovine and Porcine Oocyte as Cytoplasm Recipient - Yuda Heru Fibrianto (Universitas Gadjah Mada, 2005)
This study was conducted to increase the efficiency of canine embryo production by intergeneric somatic cell nuclear transfer (SCNT) technology. The effect of oocyte recipient for development of intergeneric canine somatic cell cloning embryos were examined. Bovine and porcine cumulus oocyte complexes (COCs) were collected from slaughterhouse ovaries and matured in TCM-199 medium depend on species. Adult dog fibroblasts collected from 3.5 years old Afghanhound dog, and cell between passage 1 and passage 10 used for intergeneric somatic cell cloning using bovine and porcine oocytes as oocyte cytoplasm donor. The result showed that oocytes from bovine and porcine can de-differentiated canine nucleus and no different between bovine and porcine oocyte in fusion and embryo development in vitro. Canine intergeneric cloned embryos developed to morula stages in vitro.